"Homes with Value": Mortgage Finance and the Reconfiguration of Home Value in Urban Mexico. (19th April 2021) - Hartman, Georgia
Abstract: Mexico is in the midst of a major urban transformation. State‐subsidized mortgage credit has facilitated the emergence of an affordable housing market and transformed the urban periphery into vast tracts of tiny concrete "social interest" housing developments. Easily available credit has allowed millions of Mexican workers to pursue the cultural and moral imperative to possess "patrimonio" by becoming homeowners. Patrimonio can be understood as a kind of inalienable possession tied to gendered notions of the family, inheritance, and economic security. Yet ballooning mortgage debts associated with these homes inverts the promise of patrimonio, turning the home into a source of economic instability and insecurity. I argue that this paradoxical situation derives from the convergence of different logics for understanding a home's value—as patrimonio, as social good, and as financialized commodity. The mortgage contract reconfigures the patrimonial desires of homeowners into a vehicle for marco‐economic growth and a source of private profits. Drawing on twenty‐two months of ethnographic field research in Mexico City and Cancún, I highlight frictions in the meanings of home as a cultural imperative, social good, and financial commodity that arise in the context of its mobilization as marketized commodity in contemporary urban Mexico.